2023
DOI: 10.3390/nu15122759
|View full text |Cite
|
Sign up to set email alerts
|

Featured Prebiotic Agent: The Roles and Mechanisms of Direct and Indirect Prebiotic Activities of Lactoferrin and Its Application in Disease Control

Abstract: Lactoferrin (LF) is a glycoprotein found in mammalian milk, and lactoferricin is a peptide derived from LF hydrolysate. Both LF and lactoferricin (LFcin) have diverse functions that could benefit mammals. Bovine LF (BLF) and BLFcin exhibit a wide range of antimicrobial activities, but most probiotic strains are relatively resistant to their antibacterial effects. BLF and BLF hydrolysate can promote the growth of specific probiotics depending on the culture conditions, the dose of BLF or BLF-related peptides, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…However, regardless of the mechanisms involved, the results obtained from testing different experimental conditions indicated that the direct prebiotic activity of lactoferrin may vary depending on factors such as bacterial strain, temperature, oxygen levels, lactoferrin iron-saturation levels, and dosage [ 138 , 139 , 140 , 141 , 142 ]. Chen et al, while exploring in vitro the prebiotic potential of bovine lactoferrin in 14 probiotics, including B. breve , L. coryniformis , L. delbrueckii , L. acidophilus , B. angulatum , B. catenulatum , and L. paraplantarum , observed a negligible effect on probiotic growth at 37 °C, but a strong lactoferrin-mediated dose-dependent restart of growth at lower temperatures (i.e., 22 °C), suggesting that the direct prebiotic effects of lactoferrin become significant when the probiotic growth is retarded by cold stress conditions [ 143 ].…”
Section: Prebiotic Activity Of Whey Proteinsmentioning
confidence: 99%
“…However, regardless of the mechanisms involved, the results obtained from testing different experimental conditions indicated that the direct prebiotic activity of lactoferrin may vary depending on factors such as bacterial strain, temperature, oxygen levels, lactoferrin iron-saturation levels, and dosage [ 138 , 139 , 140 , 141 , 142 ]. Chen et al, while exploring in vitro the prebiotic potential of bovine lactoferrin in 14 probiotics, including B. breve , L. coryniformis , L. delbrueckii , L. acidophilus , B. angulatum , B. catenulatum , and L. paraplantarum , observed a negligible effect on probiotic growth at 37 °C, but a strong lactoferrin-mediated dose-dependent restart of growth at lower temperatures (i.e., 22 °C), suggesting that the direct prebiotic effects of lactoferrin become significant when the probiotic growth is retarded by cold stress conditions [ 143 ].…”
Section: Prebiotic Activity Of Whey Proteinsmentioning
confidence: 99%
“…Lactoferrin (LF) is an 80 kDa iron-binding glycoprotein predominantly found in the milk and various exocrine fluids of mammals. It manifests diverse pleiotropic activities, encompassing anti-inflammatory, antimicrobial, antioxidant, immune-regulating, and prebiotic properties [28][29][30]. Additionally, in both low-and high-dose combinations, LF and inulin have demonstrated an additive or supra-additive effect in reducing energy intake, body weight, and adiposity in a diet-induced obese rat model [31].…”
Section: Introductionmentioning
confidence: 99%